Electrochemical disinfection using a modified reticulated vitreous carbon cathode for drinking water treatment. (January 2019) - Jin, Yanchao; Shi, Yijun; Chen, Riyao; Chen, Xiao; Zheng, Xi; Liu, Yaoxing
Abstract: A reticulated vitreous carbon (RVC) cathode modified by anodic polarization in 20 wt% H2 SO4 solution was used for drinking water disinfection under a neutral low electrolyte concentration (0.25 g/L Na2 SO4 ) condition. The contribution of the modified RVC anode and the Ti/RuO2 cathode to disinfection was investigated. The influences of current, initial Escherichia coli load, temperature and water volume were studied. The results show that H2 O2 generation increased to approximately three times using the modification of the RVC. E. coli was mainly deactivated by the H2 O2 generated at the cathode. For water with about 10 6  CFU/mL E. coli, the detection limit (<4 CFU/mL) was reached under different conditions. Increasing current could simultaneously shorten the treatment time and increase the energy consumption (EC) simultaneously. Although decreasing the initial load reduced the treatment time, the EC for per log E. coli removal increased. The time required for disinfection shortened from 3.5 to 2.5 h and the EC for per log removal decreased from 218.5 to 123.2 Wh/m 3 when the temperature increased from 20 to 40 °C. Although more time was required for disinfection, the EC decreased from 218.5 to 141.4 Wh/m 3 when the volume was doubled. Highlights: E. coli was inactivated in neutral lower salinity electrolyte (0.25 g/L Na2 SO4 ). Modified RVC cathode was the main contributor for disinfection. The anodic polarization of RVC could enhance H2 O2 generation. Raising temperature could enhance the disinfection process. The energy required for disinfection was 218.5 Wh/m 3 at 20 °C.